To add the linear expressions \( 7(n-2) + 5(n+4) + 3(n+1) \), we will first distribute the constants across the parentheses:
-
Distributing \( 7 \) in the first term: \[ 7(n - 2) = 7n - 14 \]
-
Distributing \( 5 \) in the second term: \[ 5(n + 4) = 5n + 20 \]
-
Distributing \( 3 \) in the third term: \[ 3(n + 1) = 3n + 3 \]
Now we will combine all of these results: \[ 7n - 14 + 5n + 20 + 3n + 3 \]
Next, we will combine the like terms (the \( n \) terms and the constant terms):
-
For the \( n \) terms: \[ 7n + 5n + 3n = 15n \]
-
For the constant terms: \[ -14 + 20 + 3 = 9 \]
Putting it all together, we get: \[ 15n + 9 \]
So the final answer is: \[ \boxed{15n + 9} \]